SIMULASI PROSES DEEP DRAWING CUP (BASKOM) PELAT JENIS STAINLESS STEEL 304 DENGAN MENGGUNAKAN SOFTWARE ABAQUS 6.9-3 - Sudi Winarso; Tugiman Tugiman (e-Dinamis, 2013)
AbstractIn the manufacturing process can not be separated from a loss defects such as wrinkles(wringkling), depletion (ironing), and break (fracture). Among the factors that influence theoccurrence of the defect is material factor is the mechanical properties (plasticity). Thissimulation aims to determine the nature of the material plasticity. The simulation is performedusing the software Abaqus 6.9-3. Type of material used is Stainless Steel 304 with a thicknessof 1mm, and then determining the dimensions manufacture punch, die, and blank holder inorder to obtain the best possible outcome, and be able to understand whether the resultsobtained in accordance with the simulated value tensile test results are then converted be thevalue of the actual stress and strain (true stress-strain) as an input to the simulation data. Themaximum voltage that occurs in the material Stainless Steel 304 is equal to 6.637 E +08 Pa,style suppression that occurs in the material is equal to 409.56 kN, Ultimate Tensile Strength of550.25 MPa, 282.12 MPa for Effective Stress, Maximum Shear stress at 141.06 MPa,Hydrostatic stress at 94.04 MPa, Deviatoric or Reduced Component of Stress and Tension at188.08 MPa at 284.79 kN.Keywords: Cup, Deep Drawing, ABAQUS, Stainless Steel